PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA HAPPY NOTES UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA KELAS IV SDN 106 PEKANBARU - Fitri, Annisa; Ghibran Dwi Rizqy; Nurahmi Lulasari; Lulu Riswana; Rizki Ezra Manik; Erlisnawati; Fitria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is a class action research that aims to improve the learning outcomes of fourth grade students of SDN 106 Pekanbaru in IPAS subjects. This research uses the Kemmis and Mc Taggart design which consists of four stages, namely planning, action, observation and reflection. The research technique was conducted through triangulation of techniques consisting of interviews, learning outcomes tests and field notes. The subjects of this study were 30 students consisting of 12 female students and 18 male students in class IV SDN 106 Pekanbaru in the 2024/2025 school year. The results showed an increase in learning outcomes marked by an increase in the value of students who completed KKTP by 56.67% in cycle I up to 83.88% in cycle II. Based on the results of class action research that has been carried out, it is concluded that the use of the PjBL learning model assisted by Happy Notes media can improve student learning outcomes in IPAS subjects in class IV students of SDN 106 Pekanbaru.